Direct laser deposition of stainless steel for better corrosion resistance - Shaik Muhamad Syafiq Bin Shaik Alwi (Nanyang Technological University, 2023)
This project aims to investigate the effect of direct laser deposition (DLD) on the corrosion resistance of stainless steel. Corrosion is a common problem in various industries, and stainless steel is a widely used material due to its excellent mechanical and chemical properties. However, its susceptibility to corrosion remains a significant issue affecting the components' durability and reliability. The DLD process is a promising technique for improving the corrosion resistance of stainless steel by introducing a coating layer with higher chemical stability and resistance to corrosion. The project includes preparing the stainless-steel substrate, optimizing the DLD process parameters, and characterization of the deposited layer using various analytical techniques. Electrochemical experiments in a corrosive environment are used to gauge the deposited layer's corrosion resistance. The results are compared with the uncoated substrate to determine the effectiveness of the DLD process in enhancing the corrosion resistance of stainless steel. The findings of this project will provide insights into the potential of DLD as a surface modification technique for enhancing the corrosion resistance of stainless steel. This could have significant implications for various industries, including aerospace, automotive, and biomedical, where corrosion resistance is critical for the performance and reliability of the components